Remote controlled car burglar alarm / Siti Ruslina Mohd Rusli and Yuszaini Junus - Mohd Rusli, Siti Ruslina; Junus, Yuszaini (1988)
Public safety has become a strong concern for modern living. Terrorism, robbery. Theft and fires provide the hayards that man find it difficult to curb with. In certain places especially in urban areas, protecting against this hazard has become a must and a way of life.